Potential Application of Marginal Analysis in Construction Projects - Ismail, Muhammad Marzuki; Nagapan, Sasitharan; Saim, Nur Amylia Izrin Mohd; Ismail, Mohd Firdaus (Tropical Scientific Journal, 2023)
Objective: This article discusses the marginal analysis and how it can be used to determine construction projects. It presents the features of marginal analysis with their relevant characteristics, as well as examples of how marginal analysis can be used to optimize the cost of construction projects. Finally, it presents a series of previous related research works on marginal analysis applied in the construction industry. Research Method: This research was carried out using the literature from a previous related study on the application of marginal analysis in the construction industry. Findings: Marginal analysis is a useful tool for assessing the additional costs and benefits of minor changes in the construction process. It can be used in construction projects to optimize cost, safety, environmental impact, project management, BIM technology implementation, procurement methods, project financing methods, and advanced technology implementation. Originality: It is a review work of previous studies